FIELDING’S PROVERBS: A CAUTIONARY TALE - Peete, Phor (Proverbium - Yearbook, 2012)
The attribution of Thomas Fielding’s Select Proverbs of all Nations (1824) to John Wade, the English social activist, is explored in some detail. Two persistent bibliographic errors concerning this collection are exposed along the way.